Investigating critical challenges of maintaining road infrastructure in the Limpopo Province : a case of Makhado Local Municipality - Musitha, Pandelani Mumsy (University of Limpopo, 2018)
Road infrastructure is usually regarded as an economic backbone of the society. Local government has a responsibility to ensure that local roads are maintained in order to facilitate a movement of people, goods and services. The study was undertaken on the premise that local roads in Makhado Local Municipality are not promoting safety. That is, road infrastructure in this municipality is considered to be deteriorating. It is against this background that the researcher found it worthwhile to investigate critical challenges of maintaining road infrastructure in the Makhado Local Municipality focusing on the following towns, Makhado, Vuwani, Waterval and Dzanani only excluding unpaved communities and other small townships, namely Tshikota and Vleifontein. The objectives of the research were to determine the condition and effects of municipal road infrastructure within Makhado Local Municipality; to examine the legal framework governing the local municipality in the context of road infrastructure provision and maintenance as well as to recommend strategies to address challenges of road infrastructure within the municipality. The research employed both qualitative and qualitative in nature. A purposive research sampling approach was used to determine the inclusion of relevant respondents to the study. The research found out that the status of road infrastructure affect various people of different biographical background within the four towns of Makhado Local Municipality in a similar way. In the findings, the study highlight the fact that deteriorating roads conditions are often due to the following: a lack of professionals such as engineers to perform the necessary environmental scanning and identify problems in order to design the roads that suit the area, soil, landscape and climate and that other factors affecting the road infrastructure include corruption in procurement of road infrastructure projects; a lack of accountability of municipal officials; a lack or poor community involvement; and poor monitoring and maintenance of road projects. The study recommends that individuals with knowledge, expertise and skills be employed and further provide proper monitoring of the road projects.
Thesis (MPA.) -- University of Limpopo, 2018
Keywords: Municipality; Road infrastructure; Road maintenance - South Africa - Limpopo